2014
DOI: 10.1016/j.whi.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during Pregnancy and Risk of Late Preterm Birth, Cesarean Delivery, and Hospitalizations

Abstract: Background Federal physical activity guidelines recommend at least 150 minutes of moderate-intensity exercise per week during pregnancy. We studied whether regular exercise during pregnancy is associated with preterm birth, cesarean delivery, and hospitalization during pregnancy. Methods Self-reported weekly exercise was ascertained in 3,006 women during the 3rd trimester of pregnancy. Using multivariable logistic regression, we report the relationship between regular exercise (at least 150 minutes per week)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 32 publications
0
33
0
8
Order By: Relevance
“…Cohort and cross-sectional studies suggest that moderate exercise either protects against caesarean delivery or has no impact on this outcome 51 53 55 56 75 88 92–94. In a group of well-conditioned women who regularly performed aerobics or running before pregnancy, those who continued to exercise at or above 50% of their preconception level throughout pregnancy had a lower incidence of caesarean delivery than those who discontinued their regular exercise before the end of the first trimester (6% vs 20%) 95.…”
Section: The Effect Of Exercise On Deliverymentioning
confidence: 99%
“…Cohort and cross-sectional studies suggest that moderate exercise either protects against caesarean delivery or has no impact on this outcome 51 53 55 56 75 88 92–94. In a group of well-conditioned women who regularly performed aerobics or running before pregnancy, those who continued to exercise at or above 50% of their preconception level throughout pregnancy had a lower incidence of caesarean delivery than those who discontinued their regular exercise before the end of the first trimester (6% vs 20%) 95.…”
Section: The Effect Of Exercise On Deliverymentioning
confidence: 99%
“…Positive effects have been described for cardiovascular function, weight gain during pregnancy, musculoskeletal symptoms, muscle cramps and oedema, the development of postpartum incontinence and psycho-emotional problems [5][6][7]. Shortened labour and a lower rate of operative/instrumental delivery appear to be secondary positive effects [5,8,9]. Regular exercise even in the 3rd trimester neither leads to an increased rate of premature delivery nor to increased hospitalisation [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Shortened labour and a lower rate of operative/instrumental delivery appear to be secondary positive effects [5,8,9]. Regular exercise even in the 3rd trimester neither leads to an increased rate of premature delivery nor to increased hospitalisation [8,10]. Moreover, mostly on the basis of preclinical data, positive effects on the newborn in terms of longterm risk of chronic metabolic, cardiovascular and oncological diseases are discussed [11].…”
Section: Introductionmentioning
confidence: 99%
“…Instrumental delivery or Caesarean section can have many sequelae that condition postpartum recovery. While earlier studies found no influence of exercise on type of delivery,102 103 more recent studies suggest that an association exists between exercise during pregnancy and a reduced need for Caesarean section 104 105…”
Section: Exercise and Pregnancymentioning
confidence: 96%